The deadly curse of Toco-Rey - Peretti, Frank E. (Dallas : Word Pub., 1996)
While on a quest to save a piece of history, Jay, Lila, and their father encounter hostile natives and ancient evil forces in the jungles of Central America.
"Word kids!"
5.9
3-6
3-6
740
Keywords: Supernatural -- Fiction; Jungles -- Fiction; Adventure and adventurers -- Fiction; Supernatural -- Fiction; Jungles -- Fiction; Adventure fiction